Preparation method of large-area textured lithium alloy negative electrode and metal lithium battery

By controlling the rolling conditions, the crystal surface of the lithium alloy foil is transformed, forming a prelithiation channel, which solves the problems of uneven lithium deposition and lithium dendrites caused by the traditional metal lithium negative electrode due to the uneven lattice gap, and significantly improves lithium 金属电池的循环稳定性能和安全性。

CN119495718APending Publication Date: 2025-02-21SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411667346.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The traditional metal lithium negative electrodes have problems such as uneven lithium deposition, lithium dendrites growth and battery short circuit due to the messy and uneven lattice gaps, and the existing technology is difficult to effectively solve.

Method used

By controlling the rolling temperature and folding rolling times of the roller press, controlling the folding and rolling times of different folding and rolling times, the high-density dislocation slip of the lithium metal crystal is realized, driving the crystal surface transformation of the lithium alloy foil and forming a prelithization channel And continuously alloy and dealloyate to promote uniform deposition of lithium and prevent the growth of lithium dendrites.

Benefits of technology

It significantly improves the cycle stability performance of lithium metal batteries, reduces safety risks, and achieves the effect of uniform lithium deposition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495718A_ABST
    Figure CN119495718A_ABST
Patent Text Reader

Abstract

According to the preparation method of the large-area textured lithium alloy negative electrode and the metal lithium battery, lithium metal and another metal are mixed through a melting method and heated and fired to obtain an alloy metal ingot, and the large-area textured lithium alloy foil is obtained after roller thinning and folding rolling. According to the invention, the rolling temperature and the folding and rolling times of the roller press are regulated and controlled, and different folding and rolling times are controlled, so that the lithium metal crystal with high ductility generates slippage under high-density dislocation, and the lithium alloy foil is driven to generate crystal face transformation; the obtained alloyed negative electrode material forms a pre-lithiation channel and continuously generates alloying and dealloying processes, so that lithium is easy to uniformly deposit and lithium dendrites are prevented from growing, the irregular grain boundary of a lithium metal negative electrode is eliminated, the ion transmission kinetics of the surface of the negative electrode is improved, and the cycling stability of a lithium metal battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a technology in the field of lithium metal batteries, specifically a method for preparing a large-area textured lithium alloy negative electrode and a metal lithium battery. Background Art

[0002] Traditional metal lithium anodes have high chemical reactivity and inherent lattice defects. The three crystal plane orientations (110), (200), and (211) contain different physical and chemical properties and problems such as disordered and uneven lattice gaps. Some existing technologies have made a series of improvements to lithium metal anodes, but there are few improvement strategies for lithium metal itself. The process is complicated and costly, and it is difficult to solve the problems of uneven lithium deposition, lithium dendrite growth, and even battery short circuit caused by disordered and uneven lattice gaps.

[0003] At present, some works have adopted a single alloying or texturing strategy to improve lithium metal negative electrodes. However, compared with the present invention, the existing technology cannot solve technical problems including the effective use of texturing strategies on lithium-philic alloy negative electrodes. In addition, the methods used in these works to prepare lithium metals, such as electrolysis and melting methods, are difficult to achieve large-scale continuous preparation. At the same time, it is impossible to take both strategies into account at low cost, so it is difficult to truly put them into application. Summary of the invention

[0004] The present invention aims at the problem that numerous lattice gaps in existing polycrystalline structures often lead to the growth of lithium dendrites, the generation of "dead lithium", and even cause internal short circuits in batteries. A preparation method of a large-area textured lithium alloy negative electrode and a metal lithium battery are proposed. By adjusting the rolling temperature and the number of folding and rolling times of a roller press, and controlling different folding and rolling times, the highly ductile lithium metal crystals are caused to slip under high-density dislocations, driving the lithium alloy foil to undergo crystal plane transformation. The obtained alloyed negative electrode material forms a pre-lithiation channel and continuously undergoes alloying and dealloying processes, which facilitates the uniform deposition of lithium and hinders the growth of lithium dendrites, thereby eliminating the irregular grain boundaries of the lithium metal negative electrode, improving the ion transport kinetics on the negative electrode surface, and improving the cycle stability of the lithium metal battery.

[0005] The present invention is achieved through the following technical solutions:

[0006] The invention relates to a preparation method of a large-area textured lithium alloy negative electrode and a metal lithium battery. Lithium metal and another metal are mixed by a melting method and heated and fired to obtain an alloy metal ingot, which is then rolled thin and folded to obtain a large-area textured lithium alloy foil.

[0007] The atomic ratio of the metallic lithium to another metal is 4:1-199:1.

[0008] The lithium metal purity is 98wt% or more lithium metal disc, small area lithium metal foil or lithium metal block.

[0009] The other metal is a metal disc, a small-area metal foil, a metal block or a metal powder of magnesium, silver, tin, zinc, aluminum or indium.

[0010] The heating and firing treatment is preferably carried out in a muffle furnace in an argon atmosphere. It is further preferred to heat the muffle furnace from room temperature at a rate of 1°C / min to 10°C / min, with the set temperature being 150-400°C, and then naturally cool to room temperature.

[0011] The rolling thinning is preferably achieved by a roller press in an argon atmosphere. It is further preferred to set the roller press speed to 150-500r, and the selected temperature to 15-150°C depending on the type of alloy. The final thickness of the rolled thin alloy foil is controlled to be 5-200 microns.

[0012] The folding and rolling means: folding the rolled lithium alloy foil once, paying attention to the folding direction and the rolling direction to be consistent, and then placing it in a roller press for rolling, repeating the folding-rolling steps several times to obtain a large-area textured lithium alloy foil. This step is repeated 2-30 times depending on the type of alloy.

[0013] The invention relates to the application of the lithium alloy foil prepared by the method, which is used for preparing the negative electrode of a metal lithium battery.

[0014] The metal lithium battery includes: a metal lithium battery with lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide and lithium iron phosphate as the positive electrode, a negative electrode made of the above lithium alloy foil, and an electrolyte; a metal lithium symmetric battery assembled with a pole piece made of the above lithium alloy foil and an electrolyte.

[0015] The electrolyte is, but not limited to, any one of the following: a mixed solution of 1M lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) in dioxolane (DOL) / ethylene glycol dimethyl ether (DME) and 2% LiNO3, a mixed solution of 0.2M LiPF6, 0.2M LiBF4, 0.8M lithium difluorooxalatoborate (LiDFOB) in diethyl carbonate (DEC): fluoroethylene carbonate (FEC) = 2:1 Vol%, a mixed solution of 1M LiTFSI in DME:DOL = 1:1 Vol%, or a mixed solution of 1M LiPF6 in ethylene carbonate (EC):DEC = 1:1 Vol%. Technical Effects

[0016] The present invention textures the lithium alloy over a large area, and the textured alloy structure can play the role of a skeleton, providing a continuous channel for electrons and lithium ions in the continuous alloying and dealloying processes during continuous deposition and removal, thereby improving the structural stability and inhibiting the growth of lithium dendrites; since the large-area textured lithium alloy has a single and uniform crystal structure, the transmission kinetics of lithium on the electrode surface and in the bulk phase are significantly improved, allowing lithium to be deposited uniformly; compared with the prior art, the present invention significantly reduces the safety hazards caused by the polycrystalline structure and improves the battery cycle life and stability by realizing a single crystal plane orientation structure of lithium in the textured alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the XRD pattern of the metallic lithium prepared in Example 1;

[0018] Figure 2 This is the XRD pattern of the metallic lithium prepared in Example 2;

[0019] Figure 3 This is the XRD pattern of the metallic lithium prepared in Example 4;

[0020] Figure 4 This is the XRD pattern of metallic lithium prepared in Comparative Example 2;

[0021] Figure 5 Symmetrical cells of Example 1 and Comparative Example 1 were prepared by dissolving 1M LiPF6 in EC:DEC=1:1 Vol% and 1 mA cm -2 -1mAh cm -2 EIS impedance spectrum of the battery after 50 cycles under the same conditions;

[0022] Figure 6 The symmetric battery of Example 4 and Comparative Example 2 was prepared by dissolving 1M LiPF6 in EC:DEC=1:1 Vol% and 1 mA cm -2 -1mAh cm -2 Comparison of cycle voltage-time curves under different conditions;

[0023] Figure 7 The symmetrical cells of Example 1, Example 2, Example 3 and Comparative Example 1 were dissolved in 1M LiPF6 in EC:DEC=1:1 Vol% and 1 mA cm -2 -1mAh cm -2 Under these conditions, 0.1 mA cm -2 -0.1mA cm -2 , 0.5mAcm -2 -0.5mA cm -2 The activation program has ten cycles each, and the cycle voltage-time curve comparison chart;

[0024] Figure 8 This is an optical image of the textured lithium alloy foil prepared in Example 1. DETAILED DESCRIPTION Example 1

[0025] This embodiment provides a method for preparing a large-area textured lithium alloy material, which specifically includes the following steps:

[0026] Step 1: In a glove box filled with argon, several lithium metal discs with a purity of 99 wt%, a diameter of 12 mm, and a thickness of 500 μm were weighed and weighed to a total of 3.189 g and placed in a nickel crucible, and then a magnesium metal foil with a thickness of 500 μm was cut into several pieces weighing a total of 0.587 g and placed in a nickel crucible;

[0027] Step 2: Place the crucible containing the metal in step 1 into a muffle furnace, heat it from room temperature to 320° C. at a rate of 2° C. / min, and then cool it naturally to room temperature;

[0028] Step 3: The alloy ingot obtained in step 2 is rolled thin by mechanical rolling, specifically rolling six times to gradually reduce the thickness to 100 microns to obtain a large-area polycrystalline lithium-magnesium alloy foil;

[0029] Step 4: Fold in half once in the direction of rolling in step 3, and then roll. Fold and roll six times in total. A large-area textured lithium-magnesium alloy foil is obtained;

[0030] Step 5: Roll the large-area textured lithium-magnesium alloy foil obtained by rolling into a disc with a diameter of 8 mm for assembling a symmetrical battery;

[0031] Step 6: Assemble lithium metal batteries using the textured lithium-magnesium alloy electrode obtained in step 5 for electrochemical testing; select 1M LiPF6 dissolved in EC:DEC=1:1Vol% as the electrolyte; select Celgard2500 as the separator; assemble symmetrical batteries at 1mAcm -2 -1mAh cm -2 Long cycle test under the conditions of

[0032] The above steps were all carried out in an argon glove box with a water content and an oxygen content of less than 0.01 ppm. The roller press was set at 350 r and a temperature of 25° C. The obtained alloy had a magnesium atomic ratio of 5.00%.

[0033] The textured lithium alloy negative electrode prepared in this embodiment was characterized by XRD. Figure 1 shown. Example 2

[0034] This embodiment provides a method for preparing a large-area textured lithium alloy material, which specifically includes the following steps:

[0035] Step 1: In a glove box filled with argon, a lithium metal foil with a purity of 99 wt% and a thickness of 50 μm was cut into several pieces, weighing a total of 3.873 g and placed in a nickel crucible, and a magnesium metal foil with a thickness of 500 μm was cut into several pieces, weighing a total of 0.714 g and placed in a nickel crucible;

[0036] Step 2: Place the crucible containing the metal in step 1 into a muffle furnace, heat it from room temperature to 320° C. at a rate of 2° C. / min, and then cool it naturally to room temperature;

[0037] Step 3: The alloy ingot obtained in step 2 is rolled thin by mechanical rolling, specifically rolling six times to gradually reduce the thickness to 50 microns, thereby obtaining a large-area polycrystalline lithium-magnesium alloy foil;

[0038] Step 4: folding the foil in half once along the rolling direction of step 3, and then rolling it, folding and rolling it 20 times in total, to obtain a large-area textured lithium-magnesium alloy foil;

[0039] Step 5: Roll the large-area textured lithium-magnesium alloy foil obtained by rolling into a disc with a diameter of 8 mm for assembling a symmetrical battery;

[0040] Step 6: Assemble lithium metal batteries using the textured lithium-magnesium alloy electrode obtained in step 5 for electrochemical testing; select 1M LiPF6 dissolved in EC:DEC=1:1Vol% as the electrolyte; select Celgard2500 as the separator; assemble symmetrical batteries at 1mAcm -2 -1mAh cm -2 Long cycle test under the conditions of

[0041] The above steps were all carried out in an argon glove box with a water content and an oxygen content of less than 0.01 ppm. The roller press was set at 350 r and a temperature of 25° C. The obtained alloy had a magnesium atomic ratio of 5.00%.

[0042] The textured lithium alloy negative electrode prepared in this embodiment was characterized by XRD. Figure 2 shown. Example 3

[0043] This embodiment provides a method for preparing a large-area textured lithium alloy material, which specifically includes the following steps:

[0044] Step 1: In a glove box filled with argon, several lithium metal discs with a purity of 99 wt%, a diameter of 12 mm, and a thickness of 500 μm, weighing a total of 4.703 g, are placed in a nickel crucible, and then a magnesium metal foil with a thickness of 500 μm is cut into several pieces weighing a total of 1.935 g, which are placed in a nickel crucible;

[0045] Step 2: Place the crucible containing the metal in step 1 into a muffle furnace, heat it from room temperature to 320° C. at a rate of 2° C. / min, and then cool it naturally to room temperature;

[0046] Step 3: The alloy ingot obtained in step 2 is rolled thin by mechanical rolling, specifically rolling ten times to gradually reduce the thickness to 50 microns, to obtain a large-area polycrystalline lithium-magnesium alloy foil;

[0047] Step 4: Fold in half once in the direction of rolling in step 3, and then roll. Fold and roll six times in total. A large-area textured lithium-magnesium alloy foil is obtained;

[0048] Step 5: Roll the large-area textured lithium-magnesium alloy foil obtained by rolling into a disc with a diameter of 8 mm for assembling a symmetrical battery;

[0049] Step 6: Assemble lithium metal batteries using the textured lithium-magnesium alloy electrode obtained in step 5 for electrochemical testing; select 1M LiPF6 dissolved in EC:DEC=1:1Vol% as the electrolyte; select Celgard2500 as the separator; assemble symmetrical batteries at 1mAcm -2 -1mAh cm -2 Long cycle test under the conditions of

[0050] The above steps were all carried out in an argon glove box with a water content and an oxygen content of less than 0.01 ppm. The roller press was set at 350 r and a temperature of 25° C. The obtained alloy had a magnesium atomic ratio of 10.5%. Example 4

[0051] This embodiment provides a method for preparing a large-area textured lithium alloy material, which specifically includes the following steps:

[0052] Step 1: In a glove box filled with argon, several lithium metal discs with a purity of 99 wt%, a diameter of 12 mm, and a thickness of 500 μm were weighed and placed in a nickel crucible, and 0.610 g of silver powder with a purity of 99 wt% was weighed and placed in the nickel crucible;

[0053] Step 2: Place the crucible containing the metal in step 1 into a muffle furnace, heat it from room temperature to 360° C. at a rate of 4° C. / min, and then cool it naturally to room temperature;

[0054] Step 3: The alloy ingot obtained in step 2 is rolled thin by mechanical rolling, specifically rolling for 14 times, gradually reducing the thickness to 100 microns, to obtain a large-area polycrystalline lithium-silver alloy foil;

[0055] Step 4: Fold in half once in the direction of rolling in step 3, and then roll. Fold and roll four times in total. A large-area textured lithium-silver alloy foil is obtained;

[0056] Step 5: Roll the large-area textured lithium silver alloy foil obtained by rolling into a disc with a diameter of 8 mm for assembling a symmetrical battery;

[0057] Step 6: Assemble lithium metal battery using the textured lithium silver alloy electrode obtained in step 5 for electrochemical testing; select 1M LiPF6 dissolved in EC:DEC=1:1Vol% as electrolyte; select Celgard2500 as separator; assemble symmetrical battery at 1mAcm -2 -1mAh cm -2 Long cycle test under the conditions of

[0058] The above steps were all carried out in an argon glove box with a water content and an oxygen content both lower than 0.01 ppm, the roller press was set at 400r, the temperature was 60°C, and the obtained alloy had an atomic ratio of silver element of 0.87%.

[0059] The textured lithium alloy negative electrode prepared in this embodiment was characterized by XRD. Figure 3 shown. Comparative Example 1

[0060] This comparative example provides a method for preparing a large-area lithium alloy material, which specifically comprises the following steps:

[0061] Step 1: In a glove box filled with argon, several lithium metal discs with a purity of 99 wt%, a diameter of 12 mm, and a thickness of 500 μm, weighing a total of 4.092 g, are placed in a nickel crucible, and then a magnesium metal foil with a thickness of 500 μm is cut into several pieces weighing a total of 0.617 g, which are placed in a nickel crucible;

[0062] Step 2: Place the crucible containing the metal in step 1 into a muffle furnace, heat it from room temperature to 320° C. at a rate of 2° C. / min, and then cool it naturally to room temperature;

[0063] Step 3: The alloy ingot obtained in step 2 is rolled thin by mechanical rolling, specifically rolling six times to gradually reduce the thickness to 100 microns to obtain a large-area lithium-magnesium alloy foil;

[0064] Step 4: Roll the large-area lithium-magnesium alloy foil obtained by rolling into a disc with a diameter of 8 mm for assembling a symmetrical battery;

[0065] Step 5: Assemble lithium metal batteries using the lithium magnesium alloy pole pieces obtained in step 4 for electrochemical testing; select 1M LiPF6 dissolved in EC:DEC = 1:1 Vol% as the electrolyte; select Celgard2500 as the separator; assemble symmetrical batteries at 1 mA cm -2 -1mAh cm -2 Long cycle test under the conditions of

[0066] The above steps were all carried out in an argon glove box with a water content and an oxygen content of less than 0.01 ppm. The roller press was set at 350 r and a temperature of 25° C. The obtained alloy had a magnesium atomic ratio of 5.00%. Comparative Example 2

[0067] This comparative example provides a method for preparing a large-area lithium metal foil, which specifically comprises the following steps:

[0068] Step 1: In a glove box filled with argon, a lithium metal foil with a purity of 99 wt%, a thickness of 200 μm and an area of ​​2 cm×10 cm is rolled thin by mechanical rolling, specifically rolling six times, gradually reducing the thickness to 50 μm, to obtain a large-area polycrystalline lithium metal foil; the roller press is set at 350 r and the temperature is 25° C.

[0069] Step 2: Roll the large-area lithium metal foil obtained by rolling into a disc with a diameter of 8 mm for assembling a symmetrical battery;

[0070] Step 3: Assemble lithium metal batteries using the lithium magnesium alloy pole pieces obtained in step 2 for electrochemical testing; select 1M LiPF6 dissolved in EC:DEC = 1:1 Vol% as the electrolyte; select Celgard2500 as the separator; assemble symmetrical batteries at 1 mA cm -2 -1mAh cm -2 Long cycle test was carried out under the conditions of

[0071] The textured lithium alloy negative electrode prepared in this comparative example was characterized by XRD. Figure 4 shown.

[0072] It can be seen that in different embodiments, different lithium alloys are subjected to different rolling processes to obtain a textured lithium alloy negative electrode material with a single crystal plane orientation. Figure 1 and Figure 3 As shown, the single crystal plane orientation of lithium (110) is obtained. Figure 2 The result is a single crystal orientation of lithium (200). Figure 4The XRD image of polycrystalline lithium is shown in Figure 1. The results show that the strategy of texturing the lithium alloy negative electrode of the present invention can effectively change the crystal plane orientation of the lithium alloy and realize a directional, low-cost, large-area manufacturing process.

[0073] The textured lithium alloy negative electrode prepared in Example 1 and the lithium metal negative electrode prepared in Comparative Example 1 were subjected to 1 mA cm -2 -1mAh cm -2 Symmetrical battery cycle tests under different conditions were performed and compared. Figure 5 As shown, after 50 cycles, the impedance of the lithium battery prepared by the textured lithium alloy negative electrode in Example 1 is much smaller than that in Comparative Example 1, which indicates that the texturized lithium alloy negative electrode is superior to the ordinary lithium alloy negative electrode, and can effectively reduce the impedance of the assembled battery and improve the battery cycle performance.

[0074] The textured lithium alloy negative electrode prepared in Example 4 and the lithium metal negative electrode prepared in Comparative Example 2 were subjected to 1 mA cm -2 -1mAh cm -2 Symmetrical battery cycle tests under different conditions were performed and compared. Figure 6 As shown, compared with the metallic lithium negative electrode prepared in Comparative Example 2, the symmetrical battery assembled with the textured lithium alloy negative electrode prepared in Example 4 can be stably cycled for a longer time at a lower overpotential.

[0075] like Figure 7 As shown, the symmetrical battery composed of Example 1, Example 2, Example 3 and Comparative Example 1 was subjected to 1 mA cm -2 -1mAh cm -2 Under these conditions, 0.1 mA cm was introduced in the early stage. -2 -0.1mA cm -2 , 0.5mA cm -2 -0.5mA cm -2The test results of ten cycles of activation procedures. For comparative example 1, the battery short-circuited after only 120 cycles. For Example 2, although it has a textured lithium alloy structure, it has a (200) crystal plane orientation due to the oriented single crystal, and a short circuit occurred after 270 cycles. Even so, it is better than comparative example 1. For Example 3 and Example 1, it contains 10% Mg content, which is slightly worse than Example 1 with 5% content in terms of cycle performance. The voltage of Example 3 increases sharply after 400 cycles. Example 1, which has a textured alloy structure and a (110) single crystal plane orientation, has the best battery performance and can be stably cycled for more than 450 cycles with extremely small overpotential. This result shows that lithium alloys can achieve a pole piece structure with a (110) single crystal plane orientation after being processed by a texturing strategy process. This strategy can effectively improve the cycle stability and safety performance of lithium metal batteries.

[0076] Compared with the prior art, the present method reduces the complicated process flow at high temperature. It is only necessary to mix and melt lithium metal and other metal materials, and then mechanically roll to achieve the preparation of a large-area textured lithium alloy negative electrode. In terms of process, the present invention has low cost and simple operation, can achieve continuous large-scale preparation, is easier to move towards large-scale production and can significantly improve the transmission dynamics of lithium on the electrode surface and in the bulk phase. The alloy skeleton structure will also provide a continuous channel for lithium ions, allowing lithium to be evenly deposited, ultimately improving the battery cycle life and stability, and significantly eliminating the safety hazards of lithium metal batteries.

[0077] The above-mentioned specific implementation can be partially adjusted in different ways by those skilled in the art without departing from the principle and purpose of the present invention. The protection scope of the present invention shall be based on the claims and shall not be limited by the above-mentioned specific implementation. Each implementation scheme within its scope shall be subject to the constraints of the present invention.

Claims

1. A method for preparing a large-area textured lithium alloy negative electrode, characterized in that: Lithium metal and another metal are mixed by a melting method and heated and fired to obtain an alloy metal ingot, which is then rolled thin and folded to obtain a large-area textured lithium alloy foil.

2. The method for preparing a large-area textured lithium alloy negative electrode according to claim 1, characterized in that: The atomic ratio of the metallic lithium to another metal is 4:1-199:

1.

3. The method for preparing a large-area textured lithium alloy negative electrode according to claim 1, characterized in that: The lithium metal purity is 98wt% or more lithium metal disc, small area lithium metal foil or lithium metal block; The other metal is a metal disc, a small-area metal foil, a metal block or a metal powder of magnesium, silver, tin, zinc, aluminum or indium.

4. The method for preparing a large-area textured lithium alloy negative electrode according to claim 1, characterized in that: The heating and firing treatment is to heat the muffle furnace from room temperature at a rate of 1°C / min to 10°C / min, the set temperature is 150-400°C, and then naturally cool to room temperature.

5. The method for preparing a large-area textured lithium alloy negative electrode according to claim 1, characterized in that: The rolling machine speed is set to 150-500r, the selected temperature is set to 15-150°C according to the type of alloy, and the final thickness of the rolled alloy foil is controlled to be 5-200 microns.

6. The method for preparing a large-area textured lithium alloy negative electrode according to claim 1, characterized in that: The folding and rolling process refers to folding the rolled lithium alloy foil once in the rolling direction, and then placing it in a rolling machine for rolling. Repeating the folding and rolling process several times can obtain a large-area textured lithium alloy foil. This process is repeated 2-30 times depending on the type of alloy.

Citation Information

Patent Citations

  • Preparation method of laminar composite for negative electrode of secondary metal lithium battery

    CN106654232A

  • Ultrathin lithium-zinc alloy foil and preparation method thereof

    CN111883739A

  • Metal lithium composite electrode, preparation method, application and battery

    CN114551813A

  • Ultrathin high-strength lithium-magnesium-based alloy foil as well as preparation method and application thereof

    CN116426774A

Cited By

  • Preparation method of multi-component mixed ion conductor

    CN120674466A

  • Preparation method of high-determinacy single crystal lithium metal negative electrode

    CN121451290A